The Critical Period Hypothesis for Second Language Pronunciation: A Critical Review of the Literature - المايز، مايز عبدالله (جامعة حائل, 2023)
ظهرت "فرضية الفترة الحرجة" في منتصف القرن العشرين لتفسير ظاهرة اكتساب الأطفال اللغة/ اللغات بسهولة أكبر من البالغين. ولكن رغم التراكم المعرفي والإنتاج العلمي الغزير حول هذه الفرضية خلال الخمسين عاما الماضية، إلا أنها ما تزال مثار اختلاف بين الباحثين. ومن خلال مراجعة الدراسات والبحوث العلمية النظرية والتطبيقية، تسعى هذه المقالة الاستعراضية لتقديم تحليل نقدي لهذه الفرضية من حيث صلتها باكتساب مهارات النطق في اللغة الثانية. فيستهل الباحث المقالة باستعراض تباين الباحثين في تعريف الفترة الحرجة وتحديد مدتها الزمنية، وتوضيح مدى تأثير هذه التباين على إمكانية الاستفادة من هذه الفرضية. لينتقل بعد ذلك الباحث لتوضيح أن العلاقة بين عمر التعلم والاكتساب الكامل لمهارات النطق ليست علاقة سببية، أي أن العمر لا يجب أن ينظر له بمعزل عن عوامل أخرى مترابطة مثل: الدافعية، كم ونوع المدخلات اللغوية الدروس المختصة في تعليم النطق جنس المتعلم، والتي بدروها يمكن أن تسهم بشكل كبير في عملية اكتساب مهارات النطق. ويختتم الباحث المقالة بتقديم بعض التوصيات النظرية والتعليمية المجال تعليم واكتساب اللغة. The Critical Period Hypothesis (CPH) was initially proposed in the mid-twentieth century to account for why children acquire language(s) with greater ease and proficiency than adults. Despite the profuse scholarly literature that has accumulated over the last 50 years, nonetheless, controversies surrounding the CPH have not subsided yet. This paper endeavours to critically examine the complexity that encompasses this phenomenon as it relates to the acquisition of second language ‘Pronunciation’. Drawing on existing empirical and theoretical literature, the paper first explicates the discrepancies among scholars with respect to what the CPH actually is and what age constitutes its onset and the offset points, pointing out that this lack of consensus could cast severe doubt not only over the plausibility of the CPH, but also over its utility. The paper then proceeds to illustrate that the correlation between the age of first exposure to a second language and the degree of pronunciation proficiency in that language is not causation. That is, instead of viewing age as the single explanatory factor for ultimate attainment of L2 pronunciation proficiency, age should be thought of as running in parallel with other interrelated variables, such as motivation, amount and quality of L2 input, formal pronunciation instruction, and gender. The paper finally concludes with some pedagogical and theoretical implications for the field.
Keywords: مهارات النطق -- اللغات الأجنبية -- المدخلات اللغوية